Adsorption of interacting monomers on spanning clusters of polyatomic species - Cornette, Valeria Cecilia (2009)
The adsorption-desorption process occurring on heterogeneous surfaces is studied by considering a special case where a fractal is used as adsorbent. The fractal surface is the spanning cluster corresponding to the random deposition of objects that occupy more than one site (k-mers) on a square lattice. Such a surface is characterized according to the deposited k-mer. Then, the adsorption of repulsively interacting particles adsorbed on the fractal surface is studied by using Monte Carlo simulations. Different thermodynamic quantities (adsorption isotherms, coverage susceptibility, etc.) are calculated and explained in terms of the characteristics of the substrate. A scheme to characterize the structure of the substrate by just considering the adsorption isotherm is presented and discussed.